Activation of Platelet NLRP3 Inflammasome in Crohn’s Disease - Zhang, Ge; Chen, He; Guo, Yifan; Zhang, Wei; Jiang, Qiuyu; Zhang, Si; Han, Liping; Chen, She; Xue, Ruyi (Frontiers in Pharmacology, 2021)
Patients with Crohn’s disease (CD) are inclined to have platelet hyperactivity and an increased risk of intestinal micro-thrombosis. However, the mechanisms underlying platelet hyperactivity in CD are not well understood. We investigated the assembly of platelet NLRP3 inflammasome in patients with active CD and its correlation with platelet hyperactivity. In this study, Real-time PCR and western blotting analyses uncovered that ASC, NLRP3, and active caspase-1 were significantly upregulated in platelets from patients with active CD compared with healthy subjects. As revealed by flow cytometry (FCM) and ELISA analyses, the levels of interleukin-1β in both serum and isolated platelets were elevated in patients with active CD. Co-immunoprecipitation and immunofluorescence experiments revealed an increased assembly of NLRP3 inflammasome in platelets from patients with active CD. In addition, higher levels of intracellular reactive oxygen species (ROS) were observed in these platelets by FCM. Furthermore, elevated levels of platelet P-selectin exposure and fibrinogen binding were demonstrated in patients with active CD by FCM. They were positively correlated with the protein levels of NLRP3 inflammasome components. Collectively, our results indicate that the ROS-NLRP3 inflammasome-interleukin-1β axis may contribute to platelet hyperactivity in active CD.